The Prevalence and Risk Factors of Venous Thrombosis among Hospitalized Patients: Are Wells Criteria Considered by Primary Care Physicians? - Mitra Samareh Fekri; Sobhan Mohammadi; Mojtaba Afzali; Michael Saeed (Journal of Kerman University of Medical Sciences, 2020)
Background: Deep vein thrombosis (DVT) is one of the main causes of hospital mortality which can easily be prevented. Three para clinical methods are used to confirm the diagnosis of DVT, which include D-dimer test, venous color Doppler ultrasonography and venography. This study has focused on the prevalence of confirmed DVT in lower limbs based on venous color Doppler ultrasonography and risk factors of this disease in patients under examination. Methods: This study was a retrospective cross sectional research done through reviewing the medical files of adult patients hospitalized in Afzalipour Hospital/ Kerman/ Iran in 2018. The samples included 1000 medical files. First, the number of venous color Doppler ultrasonography, and then the number of cases of confirmed DVT were recorded. Results: The prevalence of confirmed DVT in lower limbs was 17.4% or 1.74 in 1000 people. The analyses showed that the patients were different in developing DVT based on their history of surgery (P≤0001), trauma (P=0.05), history of COPD (P≤0.001) and previous DVT (P≤0.001). Conclusion: In the present study, from 357 Doppler ultrasonography orders only 62 cases resulted in lower limb DVT diagnosis, which is equal to 17.6%. It seems that the number of Doppler ultrasonography orders is relatively high. Therefore, it is recommended that more attention be paid to the clinical examinations of patients and Wells criteria to avoid ordering unnecessary para clinical services and consequently reduce the costs and also the hospitalization length. Moreover, more effective education and training of primary care physicians is suggested.